Chronic active Epstein–Barr virus infection as the initial symptom in a Janus kinase 3 deficiency child: Case report and literature review. Issue 42 (October 2017) - Zhong, Linqing; Wang, Wei; Ma, Mingsheng; Gou, Lijuan; Tang, Xiaoyan; Song, Hongmei
Abstract: Rationale: With the progress of sequencing technology, an increasing number of atypical primary immunodeficiency (PID) patients have been discovered, including Janus kinase 3 ( JAK3 ) gene deficiency. Patient concerns: We report a patient who presented with chronic active Epstein–Barr virus (CAEBV) infection but responded poorly to treatment with ganciclovir. Diagnoses: Next-generation sequencing (NGS) was performed, including all known PID genes, after which Sanger sequencing was performed to verify the results. Genetic analysis revealed that our patient had 2 novel compound heterozygous mutations of JAK3, a gene previously reported to cause a rare form of autosomal recessive severe combined immunodeficiency with recurrent infections. The p.H27Q mutation came from his father, while p. R222H from his mother. Thus, his diagnosis was corrected for JAK3-deficiency PID and CAEBV. Interventions: Maintenance treatment of subcutaneous injection of recombinant human interferon α-2a was given to our patient with 2 MU, 3 times a week. Outcomes: Interferon alpha was applied and the EBV infection was gradually controlled and his symptoms ameliorated remarkably. Our patient is in good health now and did not have relapses. Lessons: The diagnoses of PID should be taken into consideration when CAEBV patients respond poorly to conventional treatments. Good results of our patient indicate that interferon α-2a may be an alternative treatment for those who are unwilling to accept hematopoietic stem cell transplantation (HSCT) like our patient. Literature review identified 59 additional cases of JAK3 deficiency with various infections. Abstract : Supplemental Digital Content is available in the text